Digital word of mouth usage in the movie consumption decision process: the role of Mobile-WOM among young adults in Spain. Issue 2 (3rd April 2018) - Álvarez-Monzoncillo, José M.; de Haro Rodríguez, Guillermo; Picard, Robert G.
ABSTRACT: Smartphones have become important in everyday life for most activities, including marketing. Mobile devices can access the Internet to find information, recommend, generate and distribute content and are increasingly being used to inform consumer choices. Their capabilities are expanding the significance of word of mouth communication by overcoming temporal and spatial constraints of verbal communication. This paper analyzes the information-seeking behavior of young adults in Spain before, during and after the process of watching motion pictures in theaters or on various platforms. This process is linked to the generation of word-of-mouth (WOM) information that affects differently than the expert reviews on movies to the decision-making processes of consumers. WOM has changed with the advent of mobile devices and the development of social networks. This study suggests that online recommenders and the specialized cinema press have more power to influence than the general press or the blogs and discussion sites, suggesting that the effects of word of mouth are much more nuanced in the digital setting.